Sustainable open textbook models for social justice - Cox, Glenda; Willmers, Michelle; Masuku, Bianca (Frontiers in Education, 2022)
Growing inequity continues to manifest within and between higher education institutions, highlighting the plight of the disadvantaged versus the advantaged. Against this backdrop, students’ ability to access quality textbooks and educational resources with locally relevant content presents a critical equity issue. Open textbooks provide opportunities to address social justice in the classroom. Highlighting the injustices which motivated authors in the Digital Open Textbooks for Development (DOT4D) initiative at the University of Cape Town (UCT), this study uses Bovill’s (2020) framework of inclusion to examine the processes of 11 open textbook initiatives at UCT in terms of their degrees of inclusivity, with a focus on student participation. The authors draw on the work of political philosopher Nancy Fraser (2005) and her central norm of “parity of participation” in order to analyse the cases in terms of their ability to provide affirmative or transformative remedies to injustice. The data presented in this study is derived from a mixed-methods research and implementation approach, in which a survey was administered to the lead authors of the 11 open textbook initiatives. The proposals submitted by ten of these initiatives in their application for a DOT4D grant and their grant reports were also an important data source. This data, combined with insights from two rounds of in-depth interviews with five authors from the study sample provides insight into the injustices academics were grappling with and the ways in which they endeavoured to address them. This article articulates four open textbook models with varying degrees of colleague and student inclusion. Examining authorship, quality assurance and publishing activities as nodes of inclusivity, the article provides insight into the strategies open textbook authors at UCT adopt in order to address social injustice in the classroom related to access and representation. It also considers ways in which higher education institutions can address sustainability in order to support the endeavour.